Pengaruh Kondisi Keuangan, Kualitas Audit, Kepemilikan Institusional Dan Profitabilitas Terhadap Opini Audit Going Concern Pada Perusahaan Manufaktur Subsektor Metal And Allied Products Tahun 2017-2021 - Purba, Dewi Driani; Siahaan, Septony B; Damanik, Dennys Paulus; Silitonga, Ivo Maelina (Politeknik Raflesia Press, 2024)
This study aims to examine and analyze the effect of profitability on going concern audit opinions in Metal and Allied Products Sub-Sector Manufacturing companies in 2017-2021. The number of research samples is 13 manufacturing companies in the Metal and Allied Products sub-sector. Data analysis technique using logistic regression analysis. The results showed that financial condition and audit quality had a significant negative effect on going concern audit opinion. Institutional ownership and profitability have no significant positive effect on going concern audit opinion. Financial condition, audit quality, institutional ownership, and profitability have a significant effect on going concern audit opinion.